Does the temperature of beverages affect the surface roughness, hardness, and color stability of a composite resin? - Tuncer, Duygu; Karaman, Emel; Firat, Esra (European Journal of Dentistry, 2013)
Objective: To investigate the effect of beverages′ temperature on the surface roughness, hardness, and color stability of a composite resin. Materials and Methods: Fifty specimens of the Filtek Z250 composite (3M ESPE, Dental Products, St.Paul, MN, USA) were prepared and initial roughness, microhardness, and color were measured. Then the specimens were randomly divided into five groups of 10 specimens each: Coffee at 70°C, coffee at 37°C, cola at 10°C, cola at 37°C, and artificial saliva (control). After the samples were subjected to 15 min × 3 cycles per day of exposure to the solutions for 30 days, the final measurements were recorded. Results: After immersion in beverages, the artificial saliva group showed hardness values higher than those of the other groups (P < 0.001) and the microhardness values were significantly different from the initial values in all groups except for the control group. Both cola groups showed roughness values higher than the baseline values (P < 0.05), while the other groups showed values similar to the baseline measurements. When ΔE measurements were examined, the 70°C coffee group showed the highest color change among all the groups (P < 0.05). Conclusion: High-temperature solutions caused alterations in certain properties of composites, such as increased color change, although they did not affect the hardness or roughness of the composite resin material tested.
Keywords: Color stability; different beverages; different temperature; microhardness; surface roughness